Interior view of the Kärtnerthortheater in Vienna - Unknown:::Creator::::::::::::; Geissler, Maria (publisher):::Contributor:::::::::::: (Vienna; Austria; Maria Geissler)
Miniature color engraving with interior view of the Kärntnerthortheater in Vienna, Austria